Comportamento alimentar noturno e estado nutricional em estudantes do segundo grau da rede pública de ensino de Fortaleza - Silva, Francisco Girleudo Coutinho da (2015)
Night eating syndrome (NES) is currently defined by at least 25% of daily food intake after the evening meal and/ or two or more episodes of nocturnal eating per week. The prevalence of SAN in the general population has been estimated to be around 1.5%. Despite several reports that, in adults, NES is much more frequent among the obese, the nature of the relationship between NES and obesity remains unclear. Furthermore, very little is known about NES in children and adolescents. The 14-item Night Eating Questionnaire (NEQ) is a self-administered instrument that has been widely used as a screening tool for NES as well as to monitor response to treatment in patients with this condition. The purpose of this study was to develop an assessment tool suitable for adolescents and also to investigate the prevalence of NES and its relationship with obesity in this age group. A Portuguese language version of NEQ previously validated for use in Brazilian adult subjects was completed by 463 students (49, 7% males) aged between 11 and 18 (mean ± SD = 13.7 ± 1.2) y, from three high schools in Fortaleza and reapplied to 27 students, after 7 days. Reproducibility and internal consistency were evaluated by test-retest (intraclass correlation = 0.92) and Cronbach´s α = 0.73). Height and body weight were measured to calculate body mass index (BMI). Sixty five (14%) participants were underweight; 304 (65.7%) had normal weight; 48 (10.4%) were classified as overweight and 46 (9.9%) as obese. On average, NEQ global score was 14.2 ± 6.4 and intensity of symptoms compatible with the diagnosis of NES (global score ≥25) was present in 39 (8.4%) participants. There was no difference in BMI and age between individuals with symptoms of NES and those without symptoms. Compared to other students, overweight and obese participants reported less morning appetite (p <0.001) and a higher proportion of daily food consumption after dinner (p <0.001). In summary, this new version of NEQ for Brazilian adolescents has excellent reproducibility and good internal consistency. Obesity rates in High school teenagers from Fortaleza lies above the regional average. Overweight and obese adolescents report reduced morning appetite and a high proportion of food consumption after dinner. However, there is no evidence of an association between intensity of night eating symptoms and BMI in this age group. More studies of children and adolescents, using instruments with adequate measurement properties, are needed to investigate the factors related to the development of SAN and obesity in these age groups.